PEMIJAHAN IKAN GABUS (Channa striata) DENGAN RANGSANGAN HORMON GONADOTROPIN SINTETIK DOSIS BERBEDA - Ari saputra; Muslim .; Mirna Fitrani (Universitas Sriwijaya, 2015)
ABSTRACT The objective of this study is to know the best synthetic gonadotrophine hormon doses to stimulate the breeding of snakehead through observing the latent time, the number of eggs, and the percentage of fertilized eggs and the hatching percent of snakehead. This experiment was conducted in (UPR) Batanghari Sembilan in North Indralaya sub-district in Ogan Ilir regency on January until February 2015. The design of this study was completely randomized design which having three different treatments of different doses of hormone given. The doses treatments were P1 = 0.2 ml/kg fish, P2 = 0.4 ml/kg fish and P3 = 0.6 ml/kg fish with each male and female parent of fish was injected three treatment trhee times for each treatments. The result of this experiment showed that utilization of synthetic gonadotrophine hormone with different doses had significant different effect to hatching percentage did not significantly different (P<5%) to latent time, the amount of eggs, and fertilized eggs percentage of snakehead. In this experiment, the treatment P1 was the best terms of four parameters which were the latent time (27.70 hours), the amount of eggs (6,668 eggs), the fertilized eggs percentage (99.75 %), and hatching percentage (78.47 %). Futhermore, the value range of water quality during the experiment were temperature 28-320C, pH 3.7-7.0 and dissolved oxygen 3.08-5.76 ppm. Keywords : gonadotrophine hormone, snake head fish, spawning, doses